The Impact of Consumer Awareness and Halal Certification on Purchase Decision - Maulida, Rizqina; Nawawi, Kholil; Arif, Suyud (Islamic Economics Methodology, 2024)
The increasing number of Muslim residents in the city of Bogor means that people's purchasing power, especially for food and drinks, must be balanced with consumer awareness of halal food products. J.CO is one of Indonesia's local products in the food and beverage sector. Apart from that, we are committed to serving delicious and quality products. In 2018, J.CO still did not have a halal certificate from MUI. However, in May 2023, to be precise, J.CO products will already have certificates through various halal certification processes based on MUI regulations. This research was conducted with the aim of finding out the effect of halal certification and consumer awareness on purchasing decisions and consumer satisfaction for J.CO products in Bogor City. The research sample used was 100 respondents. The method used is a quantitative research method. This research shows that consumer awareness and halal certification have a significant and positive effect on purchasing decisions. The results of the t test (X1) above obtained a calculated t value > t table, namely 3.940 > 1.983 and a significance value of 0.000 < 0.05. X2 t count > t table, namely 4.252 > 1.983 and the significance value is 0.000 < 0.05. F test results in table 4.9 above, it can be seen that the calculated f value > from f table is 21.299 > 3.09 and the significance value is 0.000 < 0.05. So it can be concluded that H0 is rejected and H1 is accepted, this shows that the variable consumer awareness (X1) and halal certification (X2) have a significant and simultaneous positive influence on the Purchasing Decision variable (Y) of J.CO products.